2018
DOI: 10.1186/s11671-018-2457-x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Nanoparticle Toxicity on Their Physical and Chemical Properties

Abstract: Studies on the methods of nanoparticle (NP) synthesis, analysis of their characteristics, and exploration of new fields of their applications are at the forefront of modern nanotechnology. The possibility of engineering water-soluble NPs has paved the way to their use in various basic and applied biomedical researches. At present, NPs are used in diagnosis for imaging of numerous molecular markers of genetic and autoimmune diseases, malignant tumors, and many other disorders. NPs are also used for targeted del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
423
2
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 828 publications
(509 citation statements)
references
References 172 publications
9
423
2
17
Order By: Relevance
“…Augustine et al () reported that 4% ZnO/PVDF‐TrFE was slightly cytotoxic for MSCs and endothelial cells. Different cytotoxicity levels could be due to the properties of the nanoparticles, particle size, purity and size distribution (Sahu, Kannan, Tailang, & Vijayaraghavan, ) in addition to the polymer (Sukhanova et al, ). In this study, ZnO composite scaffolds did not have an adverse effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Augustine et al () reported that 4% ZnO/PVDF‐TrFE was slightly cytotoxic for MSCs and endothelial cells. Different cytotoxicity levels could be due to the properties of the nanoparticles, particle size, purity and size distribution (Sahu, Kannan, Tailang, & Vijayaraghavan, ) in addition to the polymer (Sukhanova et al, ). In this study, ZnO composite scaffolds did not have an adverse effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of the nanomedicines depends on the cell−NP interactions that relies on the different NPs' properties, including size, shape, composition, and surface charge . Therefore, we prepared both 2D cell model and 3D tumor cell spheroids to evaluate whether the modifications that were carried out on the LNPs affected their in vitro cytocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, the bare LNPs showed significant toxicity at 100 µg mL −1 for MDA‐MB‐231 (Figure e), and 50 and 100 µg mL −1 for A549 (Figure f) cell lines. This can be due to a higher content on carboxyl groups of the bare LNPs compared to both peptide‐functionalized LNPs that induces more toxicity to the cells, resulting in an impaired cell viability . Therefore, the peptide‐decorated LNPs were less toxic than the bare LNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to size, surface chemistry, crystalline structure, solubility, and chemical composition, factors which have been carefully reviewed elsewhere, the biological (including antimicrobial) activities of nanostructures commonly used as additives in food packaging are affected by shape. Truncated triangular silver nanoplates exhibited stronger bacterial inhibition when compared to spherical or rod‐shaped AgNPs .…”
Section: Shape Mattersmentioning
confidence: 99%